Comparative Analysis of Rrs486 and Rrs551 Wavelength Effectiveness from SNPP_VIIRS Satellite Imagery for Chlorophyll-a Mapping in Madura Strait, East Java - Apriliana, Diyah Ayu; Yuliano, Hendrikus; Wibisana, Hendrata (UPN Veteran Jatim, 2025)
This study assesses the comparative performance of two remote sensing reflectance (Rrs) wavelengths, Rrs486 and Rrs551, derived from Suomi NPP VIIRS imagery, for estimating chlorophyll-a (chl-a) concentration in the Madura Strait, East Java, Indonesia. SNPP-VIIRS data from January 2025 and in-situ chl-a measurements from 25 sampling stations were analyzed to evaluate statistical relationships between satellite-derived Rrs and field observations. Correlation results show that Rrs486 has a stronger negative relationship with chl-a (r = –0.92) than Rrs551 (r = –0.83). Empirical algorithms developed for each wavelength indicate superior performance of the Rrs486-based model, yielding R² = 0.84, RMSE = 0.0021 mg/m³, and MAPE = 6.8%. In comparison, the Rrs551-based model produced lower accuracy with R² = 0.69, RMSE = 0.0037 mg/m³, and MAPE = 11.2%. A reflectance ratio algorithm (Rrs486/Rrs551) also demonstrated strong predictive potential (R² = 0.88). Spatial mapping using the optimal Rrs486 algorithm revealed higher chl-a concentrations near coastal zones and lower values in offshore waters. Overall, the findings confirm that Rrs486 provides more reliable chl-a estimations due to its spectral proximity to chlorophyll-a absorption features, supporting improved satellite-based monitoring in tropical coastal environments.